Social work training for intervention in gender and sexual diversity: https://doi.org/10.53809/2021-01-TS-n.1-122-131 ("Temas Sociais" Journal, 2021)
National and international social service associations have been committed to protecting and preserving the rights of LGBTI people as they recognize the multiple oppressions they are related to. However, as schools of social service you need to provide training equipment on gender and sexuality, which contributes to the fact that social workers are not assigned to deal with and respond to the needs of LGBTI people. The present article therefore supports the need for social service schools to promote knowledge and develop specific skills for intervention with categories with gender identities and / or different sexual orientations, and present specifications that contribute to this educational training and professional qualification work
Keywords: LGBTI; gender; sexuality; training; social work